Parametric analysis of process loop and scanning line distance in laser cleaning of corrosion on boron steel - Irfan, Azman; Aiman, Mohd Halil; Mahadzir, Ishak@Muhammad; Moinuddin Mohammed, Quazi (Institute of Physics, 2024)
This project is a comprehensive exploration conducted within the Laser Micro Cleaning Lab at the Pekan Campus of University Malaysia Pahang. The objective of the project is to delve into laser material processing, particularly in the context of laser micro cleaning. The undertaking involves a meticulous research approach, drawing insights from authoritative and relevant journal articles sourced primarily from online platforms. The primary goal of this investigation is twofold: firstly, to scrutinize the effects of mark loops on corrosion depth in boron steel, and secondly, to examine how alterations in line distance influence the surface roughness during corrosion laser cleaning. The study will encompass a diverse range of laser cleaning parameters and materials, facilitating a comprehensive assessment of their impact on both laser mark loops and line distances. To delve deeper, a sophisticated 3D microscope analysis will be employed, focusing on evaluating corrosion depth and surface roughness. The anticipated outcomes of this research hold the promise of invaluable insights, offering optimized strategies for enhancing laser cleaning processes and achieving more efficient results.